A Bacterial Quorum Sensing Regulated Protease Inhibits Host Immune Responses by Cleaving Death Domains of Innate Immune Adaptors. - Duan,X; Boo,ZZ; Chua,SL; Chong,KHC; Long,Z; Yang,R; Zhou,Y; Janela,B; Chotirmall,SH; Ginhoux,F; Hu,Q; Wu,B; et al. (Adv Sci (Weinh), 2023)
Innate immune adaptor proteins are critical components of the innate immune system that propagate pro-inflammatory responses from their upstream receptors, and lead to pathogen clearance from the host. Bacterial pathogens have developed strategies to survive inside host cells without triggering the innate immune surveillance in ways that are still not fully understood. Here, it is reported that Pseudomonas aeruginosa induces its quorum sensing mechanism after macrophage engulfment. Further investigation of its secretome identified a quorum sensing regulated product, LasB, is responsible for innate immune suppression depending on the MyD88-mediated signaling. Moreover, it is showed that this specific type of pathogen-mediated innate immune suppression is due to the enzymatic digestion of the death domains of the innate immune adaptors, mainly MyD88, and attributed to LasB's large substrate binding groove. Lastly, it is demonstrated that the secretion of LasB from P. aeruginosa directly contributed to MyD88 degradation within macrophages. Hence, it is discovered an example of bacterial quorum sensing-regulated cellular innate immune suppression by direct cleavage of immune adaptors.